Constructing familyness: Pedagogical conversations between professional parents and adolescents - van Nijnatten, C.H.C.J.; Noordegraaf, martine (Elsevier Ltd, 2016)
This study analyzes conversation between professional ‘parents’ and of out-of-home placed adolescents in specialized foster care. Videotaped and transcribed interactions of six family treatment homes were analyzed by interactional analysis. The topics of all conversations were initiated by the adolescents and reconstructed by the parents into pedagogical moments. When parents dominated the conversation, the positive content of their contributions resulted in an active position of the adolescent. In dinner table discussions, parents tried to elicit the adolescents' perspectives, while, by joking and provoking, creating an atmosphere of familyness. The adolescents seemed familiar with talking about their perspectives, views, and future plans.
Keywords: Family treatment homes; Out-of-home-placed adolescents; Interactional analysis; Taverne